Nandi facing a Shiva Linga - Temples of India Project Team (Jio Institute, 2024)
In the mandapa (pillared hall) of the Sitaleshwar Temple, a Nandi is positioned facing the garbhagriha (sanctum sanctorum). In front of the Nandi, before the antarala (vestibule or antechamber), there is a Shiva linga (aniconic representation of Shiva) placed on a cemented pedestal.